The Effect of Cognitive-Level-Based Differentiated Instruction on Students’ Learning Outcomes in Straight-Line Equations - Juliangkary, Eliska; Yuntawati, Yuntawati; Pujilestari, Pujilestari; Winarti, Winarti (Media Pendidikan Matematika, 2026)
This study examined the effect of cognitive-level-based differentiated instruction on Grade VIII students’ learning outcomes in straight-line equation material at SMPN 1 Sambelia. A quantitative quasi-experimental design with a nonequivalent control group pretest-posttest structure was employed. Two intact classes participated: Class VIII E as the experimental group (n = 27) and Class VIII F as the control group (n = 25). The experimental group received differentiated instruction organized around cognitive levels C1-C6 over two 90-minute meetings, while the control group received conventional lecture-based instruction. Learning outcomes were measured through pretest and posttest essay tests covering remembering, understanding, applying, analyzing, evaluating, and creating. The test was developed from a C1-C6 blueprint and scored using an analytical rubric with weighted indicators for each cognitive level. The experimental mean increased from 59.81 to 79.85, whereas the control mean increased from 61.32 to 76.16. Normality and homogeneity assumptions were met, and the independent samples t-test showed a significant posttest difference favoring the experimental group, t(50) = 3.653, p = 0.001, mean difference = 3.692, Cohen’s d = 1.01, η² = 0.21. The normalized gain was 0.50 for the experimental group and 0.38 for the control group, both in the moderate category. These findings indicate that differentiated instruction, when guided by diagnostic cognitive mapping and supported through active group tasks, can improve students’ conceptual and procedural achievement in straight-line equations. The study offers empirical support for adaptive mathematics instruction in heterogeneous junior secondary classrooms.